Lexical and semantic representation of the linguistic and cultural concept “Rest” in the English, German, and Russian languages - Guseva, A.E., Khukhuni, G.T., Novikova, I.N., Popova, L.G., Shatilova, L.M., Biryukova, E.V. (Opción, 2019)
This article aims to clarify the features of the representation of the value component of the linguistic and cultural concept of “Rest” in the English, German and Russian advertising slogans. In contrast to English, in German and Russian rest is explicated semantically as travel. In the English and Russian languages, exists the possibility of semantic representation of rest as break; hobby, leisure. A distinctive feature of the English and German languages is the representation of the rest as a same: recovery. In the English language, recovery is concretized by the fact that it is accompanied by a decrease in pain.